2008
DOI: 10.1073/pnas.0711982105
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Pseudomonas aeruginosa genome evolution

Abstract: One of the hallmarks of the Gram-negative bacterium Pseudomonas aeruginosa is its ability to thrive in diverse environments that includes humans with a variety of debilitating diseases or immune deficiencies. Here we report the complete sequence and comparative analysis of the genomes of two representative P. aeruginosa strains isolated from cystic fibrosis (CF) patients whose genetic disorder predisposes them to infections by this pathogen. The comparison of the genomes of the two CF strains with those of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
592
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 453 publications
(617 citation statements)
references
References 25 publications
18
592
1
6
Order By: Relevance
“…GIs found by IslandViewer did not contain flanking direct sequences compared with our results [20]. Mathee et al [21] identified more GI regions in P. aeruginosa PAO1 and PA14 than the current study, but did not accurately localize these GIs. Mavrodi et al [22] obtained GIs with incomplete flanking DRs in P. fluorescens Pf-5, in particular, Pf0-1GI-1 was divided into 2 parts [23].…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…GIs found by IslandViewer did not contain flanking direct sequences compared with our results [20]. Mathee et al [21] identified more GI regions in P. aeruginosa PAO1 and PA14 than the current study, but did not accurately localize these GIs. Mavrodi et al [22] obtained GIs with incomplete flanking DRs in P. fluorescens Pf-5, in particular, Pf0-1GI-1 was divided into 2 parts [23].…”
Section: Discussioncontrasting
confidence: 52%
“…The genomic location of six GIs in P. aeruginosa was identical to those in our previous report [18], but their mobility was not determined. A number of studies have also described the regions of GIs in these four strains [14,[19][20][21][22][23]. These data have been presented in comparison with the 11 GIs of the present study ( Table 4).…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Insertions and deletions in the genome of strain PSE305 in comparison to the genome of strain PAO1 are summarised in Supplementary Tables 3 and 4. Many of these were located in previously reported regions of genome plasticity (Mathee et al, 2008). Most of the larger insertions corresponded to known genomic islands or prophages.…”
Section: Comparative Genomics Of Isolates Pse305 and Pse306mentioning
confidence: 99%